Pengaruh Model Pembelajaran Self Organized Learning Environment (SOLE) terhadap Kemampuan Pemecahan Masalah Matematis dan Self Confidence Peserta Didik - Yuni Khafifah Putri; Bambang Sri Anggoro; Siska Andriani (Jumper: Journal of Educational Multidisciplinary Research, 2026)
This study aims to determine the effect of the Self Organized Learning Environment (SOLE) learning model on students’ mathematical problem solving ability and self confidence. The research used a quasi-experimental method with a Nonequivalent Posttest Only Control Group Design involving 63 eighth-grade students at SMP Negeri 29 Bandar Lampung. Data were collected through essay tests and self confidence questionnaires. Instrument validity and reliability were verified using Pearson Product Moment correlation and Cronbach’s Alpha. The MANOVA hypothesis test showed: (1) a simultaneous effect of the SOLE model on both dependent variables; (2) a significant effect on mathematical problem solving ability; and (3) a significant effect on self confidence. The mean post-test score of the experimental class (79.25) was substantially higher than the control class (47.94), and the mean self confidence score of the experimental class was also higher. These results indicate that the SOLE learning model is effective in improving students’ mathematical problem solving ability and self confidence.